2016
DOI: 10.1007/s12264-015-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Neurostimulation for Depression: Techniques, Current Modalities, and Future Challenges

Abstract: Depression is the most prevalent debilitating mental illness; it is characterized as a disorder of mood, cognitive function, and neurovegetative function. About one in ten individuals experience depression at some stage of their lives. Antidepressant drugs are used to reduce the symptoms but relapse occurs in ~20% of patients. However, alternate therapies like brain stimulation techniques have shown promising results in this regard. This review covers the brain stimulation techniques electroconvulsive therapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 104 publications
0
33
0
Order By: Relevance
“…Depression is clinical disorder known to result from a disruption of brain neurochemistry (Akhtar et al, 2016 ). It is a neuronal abnormality characterized by disorders of mood, cognitive function, and neurovegatative functions and has a wide range of causes (Akhtar et al, 2016 ).…”
Section: Various Stimulation Targets For a Specific Disordermentioning
confidence: 99%
“…Depression is clinical disorder known to result from a disruption of brain neurochemistry (Akhtar et al, 2016 ). It is a neuronal abnormality characterized by disorders of mood, cognitive function, and neurovegatative functions and has a wide range of causes (Akhtar et al, 2016 ).…”
Section: Various Stimulation Targets For a Specific Disordermentioning
confidence: 99%
“…Future studies should also address the optimal settings for VNS and the best site to stimulate the vagus nerve. Parkinson's disease Approved [94][95][96] Vagus nerve stimulation (VNS) Epilepsy Approved [97,98] Depression Approved [93,99] Tinnitus Approved [100] Stroke Under investigation [101] Rheumatoid arthritis Under investigation [78] Crohn's disease Under investigation [89,102] Heart failure Under investigation [103,104] Baroreceptor stimulation Hypertension and heart failure Approved [105] Phrenic nerve stimulation Central sleep apnoea Approved [106] Sacral nerve stimulation Over Active Bladder and urinary incontinence Approved [107] Hypoglossal nerve stimulation (HNS) Obstructive Sleep Apnoea Approved [108] Spinal cord stimulation (SCS) Chronic pain Approved [109] Vagus nerve block (vBloc) Obesity Approved [110] Vagus nerve stimulation in RA / F…”
Section: The Effects Of Vagus Nerve Stimulation On Inflammation In Humentioning
confidence: 99%
“…Although there are various ways to modulate the activity of a specific brain area, such as random noise stimulation, ultrasound stimulation, electoral stimulation, and magnetic stimulation, recent research has been focusing on the latter two [76,77]. Transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) are two of the best-studied approaches for treating drug addiction and other mental disorders [76][77][78][79]. Studies have shown that stimulating dorsal lateral PFC by TMS and tDCS were effective to reduce craving, improve cognition, and ameliorate the mood states in subjects using major drugs of abuse [76,80].…”
Section: Brain Stimulationmentioning
confidence: 99%